Reply to OEF93 - Hochberg, M (Oxford Institute for Energy Studies, 2013)
The preliminary excitement surrounding Israel’s natural gas discoveries – most notably the Leviathan Field – has translated into broad speculation as policy experts surmise potential paths for Israeli natural gas development and exportation. In issue 93 of the Forum, Paritzky and Farren-Price, Elston and Stewart, and Bryza assess Israel’s potential export options, considering the political realities and geographical limitations which make a sound and feasible path to exportation particularly tricky.